Antibodies against bovine herpesvirus 4 are highly prevalent in wild African buffaloes throughout eastern and southern Africa - Dewals, B.; Gillet, L.; Gerdes, T.; Taracha, E.L.N.; Thiry, E.; Vanderplasschen, A. (Elsevier, 2005)
Bovine herpesvirus 4 (BoHV-4) has been isolated from cattle throughout the world. Interestingly, a survey of wild African buffaloes mainly from the Maasai Mara Game Reserve in Kenya revealed that 94% of the animals tested had anti-BoHV-4 antibodies [Rossiter, P.B., Gumm, I.D., Stagg, D.A., Conrad, P.A., Mukolwe, S., Davies, F.G., White, H., 1989. Isolation of bovine herpesvirus-3 from African buffaloes (Syncerus caffer). Res. Vet. Sci. 46, 337–343]. These authors also proposed that the serological antigenic relationship existing between BoHV-4 and alcelaphine herpesvirus 1 (AlHV-1) could confer to BoHV-4 infected buffaloes a protective immune response against lethal AlHV-1 infection. In the present study, we addressed two questions related to Rossiter et al. paper. Firstly, to investigate the role of the African buffalo as a natural host species of BoHV-4, the seroprevalence of anti-BoHV-4 antibodies was analysed in wild African buffaloes throughout eastern and southern Africa. A total of 400 sera was analysed using two complementary immunofluorescent assays. These analyses revealed that independently of their geographical origin, wild African buffaloes exhibit a seroprevalence of anti-BoHV-4 antibodies higher than 68%. This result is by far above the seroprevalence generally observed in cattle. Our data are discussed in the light of our recent phylogenetic study demonstrating that the BoHV-4 Bo17 gene has been acquired from a recent ancestor of the African buffalo. Secondly, we investigated the humoral antigenic relationship existing between BoHV-4 and AlHV-1. Our results demonstrate that among the antigens expressed in AlHV-1 infected cells, epitope(s) recognised by anti-BoHV-4 antibodies are exclusively nuclear, suggesting that the putative property of BoHV-4 to confer an immune protection against AlHV-1 relies on a cellular rather than on a humoral immune response.